The Effectiveness of Phytogreen System in Phytoremediation and Bioremediation Process to Enhance the Quality of Domestic Wastewater - Abdul Syukor, Abd Razak; Zularisam, A. W.; M. I. M., Said; Suryati, Sulaiman; Hasmanie, Abdul Halim (JATIT & LLS, 2015)
Human being are pollute the water body by different ways. Domestic wastewater is one of them. At present the endeavour of the use of aquatic plants to decontaminate wastewater has been attain very much attention. A study was conducted through bioremediation including a phytogreen zone to assess the capability of aquatic plants in constracted ponds for wastewater treatment. Standard methods were used for the analysis. The SPSS version 20 was used to get the mean, standard deviation and Least Significance Difference (LSD). From the study, it was found that by bioremediation process a great portion of studied parameters were removed. Moreover, from the aquatic plants it has been observed a substantial removals of pollutants. As, the phytoremediation is environment friendly, it could be used in the wastewater management of the nation.